Dynamic changes of serum protein in rats with acute intoxication of Chinese cobra snake venom by proteomic analysis - Hui Yan; Ping Xiang; Jingshuo Zhang; Liqi Xie; Min Shen (Oxford University Press, 2020)
To elucidate the toxic mechanism of snake venom at the protein level, proteomics technology was applied to investigate the effect of venom on circulation in the mammalian body. Temporal proteomic analysis was performed to profile the dynamic changes in the sera of Sprague-Dawley rats administered with Chinese cobra venom or saline. Using 8-plex iTRAQ analysis, 392 and 636 serum proteins were identified to be linearly upregulated or downregulated over time in the low-dose group and high-dose group, respectively. These proteins were mainly associated with the acute phase response pathway, complement system, and liver X receptor (LXR)/retinoid X receptor (RXR) and farnesoid X receptor (FXR)/RXR activation pathways. Compared with the low-dose group, the immune response and integrin pathways were inhibited in the high-dose group, although no obvious effect was observed. With consistently higher or lower expression in the high-dose group compared to the low-dose group throughout the whole process of venom poisoning, two proteins, Kininogen-1 (KNG1) and orosomucoid 1 (ORM1), which are involved in metabolism and immune response, occupied a core position in the pathway network and are considered venom dose-dependent biomarker candidates.